Comparative Analysis of Convection Permitting Model and Cumulus Parameterization for Simulation of Summer Precipitation over Qinghai-Xizang （Tibetan） Plateau - Ying CHEN; Xianyu YANG; Yaqiong LÜ; Jun WEN; Jianing ZHU (Gaoyuan qixiang)
The Qinghai-Xizang （Tibetan） Plateau is known as the Asian water tower.The change of its water resources has an important impact on the weather and climate in the lower reaches.Precipitation is a key role in the water cycle.Therefore， it is of great significance to accurately simulate plateau precipitation for water resources security in China.In recent years， some studies have found that the convection-permitting model （the cumulus parameterization scheme could be turned off when grid scale is less than 4 km） could improve the precipitation simulation over the Qinghai-Xizang （Tibetan） Plateau.However， the previous studies only selected 1~3 cumulus parameterization schemes for comparison.It is still unknown whether convection-permitting model is superior to any cumulus parameterization scheme.In this paper， the ability of nine cumulus parameterization schemes in WRF and convection-permitting model （CPM） in simulating the precipitation over the Qinghai-Xizang （Tibetan） Plateau in the summer of 2009 was evaluated.The results showed that the simulations overestimate the summer precipitation over Qinghai-Xizang （Tibetan） Plateau in 2009， and the error was about 0.4~2 mm·d-1.The over simulation of CAPE and latent heat flux in Qinghai-Xizang （Tibetan） Plateau may be one of the reasons for the overestimations.Among all simulations， the G3 cumulus parameterization scheme has the best simulation of the mean precipitation the mean precipitation and the dinural cycles precipitation and it can can better capture the precipitation intensity， spatial distribution， precipitation area and diurnal cycles of the mean precipitation.CPM showed overall the second best precipitation simulation following G3 cumulus parameterization scheme， which can not effectively improve the simulation of diurnal cycles of precipitation， but can improve the simulation of precipitation frequency.In different plateau ecological regions， all simulations cannot reasonably simulate the precipitation in the desert area and the southern foot of the Himalaya， but compared with the cumulus parameterization schemes， CPM can greatly reduce the error in the desert area.In other regions， CPM and Tiedtke cumulus parameterization scheme performed well.Considering the mean precipitation and precipitation frequency， the CPM， Tiedtke and G3 cumulus parameterization scheme have the minimum simulation error for precipitation in different regions and intensity.Therefore， we recommend to adopt G3 or Tiedtke cumulus parameterization schemes in simulating summer precipitation over the Qinghai-Xizang （Tibetan） Plateau， and when the computational resources are allowed， the high-resolution CPM can be considered to improve the precipitation frequency simulations.